2019
DOI: 10.1002/anie.201909832
|View full text |Cite
|
Sign up to set email alerts
|

A Lattice‐Oxygen‐Involved Reaction Pathway to Boost Urea Oxidation

Abstract: The electrocatalytic urea oxidation reaction (UOR) provides more economic electrons than water oxidation for various renewable energy‐related systems owing to its lower thermodynamic barriers. However, it is limited by sluggish reaction kinetics, especially by CO2 desorption steps, masking its energetic advantage compared with water oxidation. Now, a lattice‐oxygen‐involved UOR mechanism on Ni4+ active sites is reported that has significantly faster reaction kinetics than the conventional UOR mechanisms. Combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
179
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(182 citation statements)
references
References 25 publications
3
179
0
Order By: Relevance
“…utilized high‐valence transition‐metal Ni 4+ sites that could trigger lattice oxygen at the highly active sites to couple with the *CO intermediate. [ 232 ] Notably, the Ni 4+ active sites showed ultrahigh current density and TOF values toward the UOR compared to those of the Ni 3+ active sites. The DFT calculations also revealed that the lattice‐oxygen atoms in the Ni 3+ OOH surface did not participate in the reactions, while on the NiOO surface, the lattice oxygen reacted with the *CONNH 2 intermediate to form line‐type adsorbed CO 2 molecules; this result lowers the electrocatalytic potentials and energy barriers of the potential‐independent regenerations of the active sites.…”
Section: Discussionmentioning
confidence: 99%
“…utilized high‐valence transition‐metal Ni 4+ sites that could trigger lattice oxygen at the highly active sites to couple with the *CO intermediate. [ 232 ] Notably, the Ni 4+ active sites showed ultrahigh current density and TOF values toward the UOR compared to those of the Ni 3+ active sites. The DFT calculations also revealed that the lattice‐oxygen atoms in the Ni 3+ OOH surface did not participate in the reactions, while on the NiOO surface, the lattice oxygen reacted with the *CONNH 2 intermediate to form line‐type adsorbed CO 2 molecules; this result lowers the electrocatalytic potentials and energy barriers of the potential‐independent regenerations of the active sites.…”
Section: Discussionmentioning
confidence: 99%
“…For the O 1s spectra of P-LMNO and M-LMNO samples (Figure 1 f), relative intensity of the peak at 531.66 eV increases from 12.7 % to 18.9 % after surface treatment, [14] suggesting the production of oxygen vacancies. [15] The precise level of oxygen defect is confirmed by Iodometry titration. [16] The oxygen non-stoichiometry (d) of M-LMNO sample is 0.189, which is significantly higher than that of P-LMNO .…”
mentioning
confidence: 84%
“…The shortened RuO and IrO metal ligand bonds can increase the covalency of metal–oxygen bonds due to the lowered metal d states that are closer to oxygen 2p‐band centers (Figure S5, Supporting Information), and thus facilitate the generation of metal‐bonded electrophilic oxygen species. [ 22–25 ]…”
Section: Figurementioning
confidence: 99%